Real-World Experience of Tofacitinib and Baricitinib Use in Alopecia Areata in Greek Population: A Retrospective Analysis With Focus on Safety - Zoe Apalla; Efterpi Zafiriou; Effimia Zagkliverinou; Angeliki-Viktoria Ro; Polyxeni Gidarokosta; Niki Ntavari; Stella Sakellaropoulou; Maria Boziou; Anastasia Emvalomati; Eirini Kyrmanidou; Elizabeth Lazaridou (Mattioli1885, 2024)
Introduction: The introduction of Janus Kinase inhibitors (JAKi) seems to revolutionize the field of alopecia areata (AA) therapeutics. However, real-world data are still missing. Objectives: To provide evidence about effectiveness and safety of tofacitinib and baricitinib in AA in real-world settings and describe baseline disease characteristics and patients profiles that are considered good candidates for JAKi in the daily practice. Furthermore, we intended to investigate potential correlations between baseline characteristics and treatment outcomes. Methods: We retrospectively reviewed the databases of two tertiary Hospitals in Greece, to identify individuals of any age currently being treated with systemic JAKi for severe AA. Results: We identified 42 individuals, including 3 adolescents. In our cohort, 52.3% (22/42) were under tofacitinib and 47.6% (20/42) under baricitinib treatment. Efficacy analysis was performed on the subgroup of 30 patients that had completed at least a 3-month follow-up on treatment. In the latter group, mean time on treatment was 10 months. Mean Severity of Alopecia Tool and mean Dermatology Life Quality Index scores decreased from 84.46% and 12.86 at baseline, to 43.26% and 6.63, respectively. Complete response (CR) was recorded in 4 (13.33%), partial in 12 (40%) and no response in 14 patients (46.66%), correspondingly. Seventeen out of 42 (40.5%) individuals in total, reported at least 1 adverse event. No patient required hospitalization. Among 15 patients (35.7%) who got COVID-19, one suffered from serious infection. The 3 adolescents achieved CR with no significant adverse events. Conclusions: Real-world data suggest efficacy and safety of JAKi in severe forms of AA. Tolerability is optimal in younger individuals.